ANALISIS PERUBAHAN TARIF PPH FINAL TERHADAP KEPATUHAN WAJIB PAJAK PENGHASILAN - Yeti Apriliawati; Rahma Nazila Muhammad (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
The effect of changes in tax rates on income taxpayer compliance is addressed in this research. The analysis used the quantitative comparative approach and the population is the tax offices (KPP) within the scope of the Kantor Wilayah Direktorat Jenderal Pajak (Kanwil DJP) Jabar 1. The data collected using purposive sampling are secondary in the form of tax revenue reports and taxpayer compliance, which is 18 months each, before and after the regulation implemented. Descriptive statistics, normality test as well as Wilcoxon signed rank test are used to the data analysis techniques used. The renewal is the reduction to 0.5 percent of the final income tax rate that is the purpose of Law No. 23 of 2018 enactment. The finding reveals that the changes in tax rates have a significant effect on taxpayer compliance. This outcome is expected to be a consideration in future policymaking related to the tax rate.